Peran BPBD dalam Penanganan Bencana Angin Kencang di Kecamatan Mungkid Kabupaten Magelang - Hasan, Saipullah; Khusaini, Ilham; Febrianti, Aisyah; Damayanti, Tiara (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2024)
Disaster potentials that must be watched out for in Magelang Regency include Mount Merapi Eruptions, Flash Floods and Rain Lava, Landslides, Forest and Land Fires, and Strong Winds. Therefore, in reducing the impact and providing services, the Regional Disaster Management Agency (BPBD) of Magelang Regency has the function of coordinator, command and implementer in disaster management from the pre-disaster, emergency response, and post-disaster stages. This study aims to describe how BPBD Magelang Regency deals with disasters, especially strong winds. This study uses a qualitative method with a descriptive approach by collecting data through interviews and observations with informants from affected residents and the BPBD. The results of this study are that the BPBD of Magelang Regency carries out disaster management activities starting from the pre- disaster, emergency response and post-disaster stages in strong wind disasters. Then to make it easier for the public to access information about disasters, BPBD Magelang Regency has created an application called Sistem Informasi Kebencanaan Kabupaten Magelang (SIKK).